Na,K-ATPase mediated and cardiotonic induced signaling in health and disease - Trant, Jordan; Lowery, Jenna Beth; Morales-Sosa, Pedro; Blanco, Gustavo (Frontiers in Physiology, 2025)
In the late 1950’s, Na,K-ATPase (NKA) was discovered as the active transport system that establishes and maintains the transmembrane Na+ and K+ gradients necessary for cell survival and function. Almost 70 years later, a novel unexpected function for NKA was unveiled, when it was shown that NKA has the amazing versatility of playing a role beyond its classical “ion pumping” function to also serve as the receptor and signal transducer for the effects of cardiotonic steroids (CTS) in cells. Since then, the field of NKA research expanded into a new dimension. The additional unexpected finding that CTS are commonly present in the body fluids of mammals inspired investigators to further study the CTS-induced and NKA-mediated pathway, its mechanisms of action, effects in cells, and importance to tissue and body physiology. Therefore, a vast amount of information has accumulated in recent years. In this article, we attempt to review the most current information available, focusing on the effects of CTS and NKA signaling in physiological and pathological states. We also discuss controversies, unsolved issues, and future directions of this fascinating area of research.